Formation Issues and Development Prospects Contractual Base of Eurasian Economic Union - AMIRBEK, Kamshat; KUBEYEV, Yerkin; BOZHKARAULY, Altai (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505/jarle.v9.3(33).06, 2018)
This article sets the task to consider the main issues of the formation and development of the legal framework of the regional integration association of states – the Eurasian Economic Union (EAEU). The development of international economic integration is impossible without a legal framework, since it is through bilateral and multilateral treaties, as well as domestic legislation, that the states parties to international economic integration carry out political decisions and ideas into real life. Prospects for the development of the Eurasian Economic Union require an analysis of new approaches to integration interaction, as well as the solution of certain legal problems. First of all, it concerns the legal support of the functioning of both the EAEU itself and the enactment of acts of its bodies. This article focuses on solving many legal problems in the framework of the implementation of customs cooperation between the Member States of the Union, as well as the adoption of national acts, the introduction of changes and amendments to national legislation.